St Peter's, Barton-upon-Humber, Lincolnshire Volume 1 : History, Archaeology and Architecture - Rodwell, Warwick (Historic England, 2011)
St Peter's, Barton-upon-Humber, is a redundant medieval church in the care of English Heritage. As a result of a major program of research carried out between 1978 and 2007, it is now the most intensively studied parish church in the UK. Excavations between 1978 and 1984 investigated most of the interior of the building, as well as a swathe of churchyard around its exterior. At the same time, a stone-by-stone record and detailed archaeological study of the fabric and furnishings of the church was undertaken, continuing down to 2007. The twin aims of the project were to understand the architectural history and setting of this complex, multi-period building (Volume 1, Parts 1 and 2) and to recover a substantial sample of the population for palaeopathological study (Volume 2). An extensive program of historical and topographical research also took place in order to set the archaeological evidence firmly in context.